FORMING DIVERSITY AWARENESS THROUGH MULTICULTURAL DIMENSION - Muhammad Hifdil Islam (UNZAH Genggong, 2023)
This article has the aim to explain, analyze and interpret about how understanding of multicultural dimension can form the diversity awareness of people. This article is a library research that uses a qualitative approach. This article show that are strata dimensions in multicultural structures such as macro culture, micro culture and diversity. Country and nation is called the macro culture dimension. The macro culture itself is built by a collection of cultures that occupy the country (macro culture). while the dimensions in the micro culture are filled with the dimensions of diversity that exist in each individual which is called the diversity of individual. Diversity itself forms a culture which is then included in the category of microculture (group culture) and then microculture will form the national culture of a country so that it is then called macroculture. So then in forming the identity of a nation can be started from the formation of one's individual identity. If individual diversity can be understood and realized by other individuals, then mutual awareness, understanding and respect for diversity at the microculture and macroculture dimension can be formed.